First Clinical Use of the Redesigned HeartMate® II Left Ventricular Assist System in the United States: A Case Report - Frazier, O. H. (2004)
Axial flow ventricular assist devices show great promise as a potential treatment for patients with end-stage heart failure. The HeartMat® II system, redesigned on the basis of initial clinical experiences in Europe, is now in clinical trials in the United States. We report on the 1st use of the newly redesigned HeartMate II in the United States. The system has unique features, which include an accurate flow estimator and the ability to automatically detect and correct excessive left ventricular unloading. The new design also incorporates changes in the texturing of the blood-contacting surfaces to prevent thrombosis. The implantation technique and configuration are similar to those of the HeartMate XVE LVAS and require a median sternotomy for access. The 1st patient to receive the device in the United States has had an uncomplicated perioperative course and now awaits transplantation.